2007
DOI: 10.3354/dao076163
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping spring viraemia of carp virus and other piscine vesiculo-like viruses using reverse hybridisation

Abstract: A simple nylon membrane-based DNA macroarray was developed to genotype spring viraemia of carp virus (SVCV) and related viruses. Twenty-six viruses were genotyped using the array, and the results were confirmed by phylogenetic analysis of a 426 bp partial glycoprotein gene sequence. The array was not only capable of discriminating between the 4 main genogroups of cyprinid vesiculo-type viruses described previously, but also accurately sub-type the SVC viruses assigned to Genogroup I. The assay offers a practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 9 publications
0
11
0
1
Order By: Relevance
“…The sequences of the 550 bp region of the G gene of Czech isolates were identified as SVCV or pike fry-like rhabdovirus by the Basic Local Table 1). Phylogenetic analysis of the 401 nt sequences (corresponding to nucleotides 3545 to 3945 of GenBank sequence U18101) of newly and previously isolated vesiculo viruses (Björklund et al 1996, Stone et al 2003, Garver et al 2007, Miller et al 2007, Sheppard et al 2007, Teng et al 2007, Warg et al 2007, Yue et al 2008, Basic et al 2009) was done, as this allowed most isolates for which sequence data is available to be included. Phylo genetic analyses were also performed with subsets of the isolates for which 550 nt (nucleotides 3498 to 4047 of GenBank sequence U18101) and 520 nt (nucleotides 3498 to 4017 of GenBank se quence U18101) were available.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The sequences of the 550 bp region of the G gene of Czech isolates were identified as SVCV or pike fry-like rhabdovirus by the Basic Local Table 1). Phylogenetic analysis of the 401 nt sequences (corresponding to nucleotides 3545 to 3945 of GenBank sequence U18101) of newly and previously isolated vesiculo viruses (Björklund et al 1996, Stone et al 2003, Garver et al 2007, Miller et al 2007, Sheppard et al 2007, Teng et al 2007, Warg et al 2007, Yue et al 2008, Basic et al 2009) was done, as this allowed most isolates for which sequence data is available to be included. Phylo genetic analyses were also performed with subsets of the isolates for which 550 nt (nucleotides 3498 to 4047 of GenBank sequence U18101) and 520 nt (nucleotides 3498 to 4017 of GenBank se quence U18101) were available.…”
Section: Methodsmentioning
confidence: 99%
“…Phylogenetic analyses based on the 401 nt, as well as the 550 nt, region of the G gene showed that all Czech vesiculovirus isolates, except for the barbel isolate (V-630), were grouped with the representative SVCV isolates (Björklund et al 1996, Stone et al 2003, Garver et al 2007, Miller et al 2007, Sheppard et al 2007, Teng et al 2007, Warg et al 2007, Yue et al 2008, Basic et al 2009) in Genogroup I (Fig. 2) and therefore should be classified as SVCV.…”
Section: Sequencing and Phylogenetic Analysismentioning
confidence: 99%
See 3 more Smart Citations